2020
DOI: 10.3390/antiox9080768
|View full text |Cite
|
Sign up to set email alerts
|

Cotinine and 6-Hydroxy-L-Nicotine Reverses Memory Deficits and Reduces Oxidative Stress in Aβ25-35-Induced Rat Model of Alzheimer’s Disease

Abstract: The nicotinic derivatives, cotinine (COT), and 6-hydroxy-L-nicotine (6HLN), showed promising cognitive-improving effects without exhibiting the nicotine’s side-effects. Here, we investigated the impact of COT and 6HLN on memory impairment and the oxidative stress in the Aβ25-35-induced rat model of Alzheimer’s disease (AD). COT and 6HLN were chronically administered to Aβ25-35-treated rats, and their memory performances were assessed using in vivo tasks (Y-maze, novel object recognition, and radial arm maze). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 127 publications
(200 reference statements)
1
26
0
Order By: Relevance
“…Similarly, due to structural resemblance with NIC, the anxiolytic properties of COT and 6HLN showed in this study could be associated with the binding to α4β2 and α7 nAChRs. In a recent study, we showed, using in silico tools, that these nicotinic derivatives might bind to α4β2 and α7 nAChRs with similar or higher affinity than NIC [ 33 ]. The COT effects on anxiety-like behavior were investigated in a mouse model of post-traumatic stress disorder (PTSD) induced by fear conditioning [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, due to structural resemblance with NIC, the anxiolytic properties of COT and 6HLN showed in this study could be associated with the binding to α4β2 and α7 nAChRs. In a recent study, we showed, using in silico tools, that these nicotinic derivatives might bind to α4β2 and α7 nAChRs with similar or higher affinity than NIC [ 33 ]. The COT effects on anxiety-like behavior were investigated in a mouse model of post-traumatic stress disorder (PTSD) induced by fear conditioning [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that both COT and 6HLN ameliorated the cognitive deficits in a rat model of AD induced by intracerebroventricular (i.c.v.) infusion of Aβ 25–35 peptide, and this effect might be related to the binding of α7 and α4β2 nAChRs [ 33 ]. Our group also evaluated the effects of chronic administration of 6HLN on spatial memory in normal Wistar rats using specific hippocampus-dependent tasks, such as Y-maze or radial arm maze [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Aβ fragment 25–35 (Aβ25–35) is also involved in the pathogenesis of AD [ 112 , 113 ]. Researchers have investigated the neuroprotective effect of nobiletin against Aβ25-35-induced neuronal cell damage [ 114 ].…”
Section: Nobiletinmentioning
confidence: 99%